Outcome of root canal treatment using Bioceramic sealer and resinbased sealer: An observational analytical study - Gautam, Suman; Thapa, Asha; Joshi, Rojin; Joshi, Barsha (Nepal Medical College Journal, 2022)
The proper shaping and cleaning followed by well-sealed root canal system is desired for successful outcome of the endodontic treatment. With the advent of Bioceramic sealers and their beneficial biological properties, they have been widely incorporated in clinical practice. So, the purpose of this study was to find out the difference in the healing outcome of root canal treatments and retreatments carried out with either single cone obturation technique (SCO) or warm vertical compaction technique (WVC). This was observational analytical study (Cohort study), carried out in private practice. The patients were recalled at-least at six months. When association of healing with type of sealer was considered there was a statistically significant association between healing potential and type of sealer (p-value 0.03). Kaplan -Meier analysis for time to healing showed that with progress of time probability of healing was seen to be more in bioceramic sealer group. Within the limitations of this study the SCO had good healing potential and can be used as a safe alternative in obturation.